Multicenter phase 2 study of patupilone for recurrent or progressive brain metastases from non–small cell lung cancer. Issue 23 (26th August 2015) - Nayak, Lakshmi; DeAngelis, Lisa M.; Robins, H. Ian; Govindan, Ramaswamy; Gadgeel, Shirish; Kelly, Karen; Rigas, James R.; Peereboom, David M.; Rosenfeld, Steven S.; Muzikansky, Alona; Zheng, Ming; Urban, Patrick; et al.
Abstract : BACKGROUND: Treatment options for patients with non–small cell lung cancer (NSCLC) with brain metastases are limited. Patupilone (EPO906), a blood‐brain barrier–penetrating, microtubule‐targeting, cytotoxic agent, has shown clinical activity in phase 1/2 studies in patients with NSCLC. This study evaluates the efficacy, pharmacokinetics, and safety of patupilone in NSCLC brain metastases. METHODS: Adult patients with NSCLC and confirmed progressive brain metastases received patupilone intravenously at 10 mg/m 2 every 3 weeks. The primary endpoint of this multinomial 2‐stage study combined early progression (EP; death or progression within 3 weeks) and progression‐free survival at 9 weeks (PFS9w) to determine drug activity. RESULTS: Fifty patients with a median age of 60 years (range, 33‐74 years) were enrolled; the majority were men (58%), and most had received prior therapy for brain metastases (98%). The PFS9w rate was 36%, and the EP rate was 26%. Patupilone blood pharmacokinetic analyses showed mean areas under the concentration‐time curve from time zero to 504 hours for cycles 1 and 3 of 1544 and 1978 ng h/mL, respectively, and a mean steady state distribution volume of 755 L/m 2 . Grade 3/4 adverse events (AEs), regardless of their relation with the study drug, included diarrhea (24%), pulmonary embolisms (8%), convulsions (4%), and peripheral neuropathy (4%). All patients discontinued the study drug: 31 (62%) for disease progression and 13 (26%) for AEs. Twenty‐five of 32 deaths were due to brain metastases. The median time to progression and the overall survival were 3.2 and 8.8 months, respectively. CONCLUSIONS: This is the first prospective study of chemotherapy for recurrent brain metastases from NSCLC. In this population, patupilone demonstrated activity in heavily treated patients. Cancer 2015;121:4165–4172. © 2015 American Cancer Society . Abstract : This is the first prospective study of chemotherapy for recurrent brain metastases from non–small cell lung cancer. In this population, patupilone demonstrates activity in heavily treated patients.